Consumer Protection in Dental Health Services: An Analysis of Dentists' Practices in Indonesia - Nuraeni, Yeni; Sihombing, Lasmin Alfies (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
This study aims to explore the legal protection for consumers who use the services of dentists for braces in Indonesia. People need good dental health services, but many turns to dentists who offer more affordable prices without understanding the risks involved. Dentists are legally only allowed to make and install removable dentures, while medical procedures such as braces and veneers are outside their authority. This results in many consumers experiencing serious health problems, such as swollen gums and infections, but most patients do not file complaints or lawsuits due to a lack of understanding of their rights. This study includes a normative review of applicable legal regulations, including Law Number 8 of 1999 concerning Consumer Protection, which regulates the rights and obligations of consumers and business actors. The results show that dentists have a responsibility to provide services that meet standards, as well as an obligation to provide compensation if losses occur due to negligence. The public's readiness to file criminal charges against dentists who violate the law is also identified as a problem. Therefore, educational efforts are needed for the public to understand the risks of using the services of untrained dentists and the importance of choosing services from certified professionals. This research is expected to provide insight into legal protection for consumers and increase awareness of safe dental health practices.